2013
DOI: 10.1123/jsm.27.4.316
|View full text |Cite
|
Sign up to set email alerts
|

Officiating Attrition: The Experiences of Former Referees Via a Sport Development Lens

Abstract: Referees are key sport personnel who have important responsibilities both on-and off-the field.Organized competition would not survive without referees, yet little is known about what cause referees to discontinue in the role. This research examines the experiences of former referees so that managers may better understand strategies that might encourage more referees to be retained. Fifteen previous basketball referees were interviewed about their refereeing experience. Ten themes emerged that were related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
110
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 64 publications
(130 citation statements)
references
References 38 publications
(63 reference statements)
14
110
0
6
Order By: Relevance
“…To date, though, the majority of the research in the officiating context has examined only male officials (e.g., Kellett and Warner 2011;Rainey 1999). As the global shortage of officials persists (e.g., American Sport Education Program 2011; Kendall et al 2009), the survival of sports remains dependent upon strategies to recruit and retain officials (Titlebaum et al 2009;Warner et al 2013). Further, addressing the lack of women in officiating roles would both help alleviate the shortage while simultaneously promoting greater workplace gender equity.…”
Section: Gender Equity In the Sport Contextmentioning
confidence: 99%
See 4 more Smart Citations
“…To date, though, the majority of the research in the officiating context has examined only male officials (e.g., Kellett and Warner 2011;Rainey 1999). As the global shortage of officials persists (e.g., American Sport Education Program 2011; Kendall et al 2009), the survival of sports remains dependent upon strategies to recruit and retain officials (Titlebaum et al 2009;Warner et al 2013). Further, addressing the lack of women in officiating roles would both help alleviate the shortage while simultaneously promoting greater workplace gender equity.…”
Section: Gender Equity In the Sport Contextmentioning
confidence: 99%
“…Similarly, Kellett and Warner (2011) found FEMALE OFFICIALS 7 that developing a sense of community among current Australian Rules Football umpires was crucial to their retention. In their investigation of former U.S. based officials, Warner et al (2013) found that officials dropped out of the profession because of a perceived lack of referee community, managerial decision-making, and a lack of mentoring and continuing education.…”
Section: Inequity Of Policiesmentioning
confidence: 99%
See 3 more Smart Citations